Expeditious and eco-friendly hydrothermal polymerization of PEDOT nanoparticles for binder-free high performance supercapacitor electrodes. Issue 111 (21st November 2016) - Rajesh, Murugesan; Raj, C. Justin; Kim, Byung Chul; Manikandan, Ramu; Kim, Sung-Jin; Park, Sang Yeup; Lee, Kwangsoo; Yu, Kook Hyun
Abstract : Rational synthesis of different nanostructured PEDOT by a simple, efficient and environmentally benign hydrothermal polymerization was proposed to fabricate high performance binder-free supercapacitor electrodes. Abstract : Poly(3, 4-ethylenedioxythiophene) (PEDOT) is a promising conjugated polymer that has attracted attention because of its outstanding electronic properties, useful for a wide range of applications in energy storage devices. However, synthesis of high-quality PEDOT occurs via vapour phase polymerization and chemical vapour deposition techniques using extrinsic hard templates or complicated experimental setups. This study introduces a simple hydrothermal polymerization technique using ferric chloride (FeCl3 ) as an oxidizing agent to overcome the above drawback, which results in good conductive, crystalline PEDOT nanodendrites and nanospheres. The effects of varying the molar ratio of FeCl3 oxidant were investigated in terms of the structural, morphological and electrochemical properties of PEDOT. The supercapacitive performance of the as-polymerized PEDOT nanostructures was determined by fabricating an electrode without the aid of organic binders or conductive additives. PEDOT nanodendrites polymerized using 2.5 molar ratio of FeCl3 demonstrated enhanced electrochemical performance with a maximum specific capacitance of 284 F g −1 with high energy density of 39.44 W h kg −1 at 1 A g −1 current density in 1 M H2 SO4 electrolyte. Moreover, the sample possessed higher conductivity, better specific surface area, improved electrochemical properties, comparable crystallinity, and excellent cycling stability after 5000 charge/discharge cycles than the other PEDOT nanostructures. Importantly, the results establish that these materials afford good redox behaviors with better conductivity suitable for the development of an organic electrode-based supercapacitor with high specific charge capacity and stability.